2021
DOI: 10.1371/journal.pgen.1009431
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of fish oil supplementation on lipid traits in 81,246 individuals reveals new gene-diet interaction loci

Abstract: Fish oil supplementation is widely used for reducing serum triglycerides (TAGs) but has mixed effects on other circulating cardiovascular biomarkers. Many genetic polymorphisms have been associated with blood lipids, including high- and low-density-lipoprotein cholesterol (HDL-C, LDL-C), total cholesterol, and TAGs. Here, the gene-diet interaction effects of fish oil supplementation on these lipids were analyzed in a discovery cohort of up to 73,962 UK Biobank participants, using a 1-degree-of-freedom (1df) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Although there is a growing body of literature showing the beneficial effect of fish-oil consumption (such as a higher level of n-3 LCPUFA in the blood associated with a lower risk of heart disease), high blood levels of n-3 LCPUFA can be detrimental for some individuals depending on their genotype in the context of lipid profiles [ 70 ]. A recent study reported that omega-3 supplementation can either aid in reducing blood triglycerides or increase blood triglycerides depending on the genotypes of four variants for the GJB2 , SLC12A3 , ABCA6 , and MLXIPL genes in individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a growing body of literature showing the beneficial effect of fish-oil consumption (such as a higher level of n-3 LCPUFA in the blood associated with a lower risk of heart disease), high blood levels of n-3 LCPUFA can be detrimental for some individuals depending on their genotype in the context of lipid profiles [ 70 ]. A recent study reported that omega-3 supplementation can either aid in reducing blood triglycerides or increase blood triglycerides depending on the genotypes of four variants for the GJB2 , SLC12A3 , ABCA6 , and MLXIPL genes in individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach identified 846 significant GEIs, many of which involved a set of highly correlated exposures (discussed further below). The large sample size of UKB provides the statistical power needed to identify interactions and has supported genome-wide GEI discovery in investigations of anthropometric and cardiometabolic phenotypes [21][22][23][24] . However, the scale of this population also means that spurious GEIs induced by even small statistical artifacts or biological confounders may reach statistical significance, as demonstrated by Tyrell and colleagues 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These gene expression changes were accompanied by a decrease in circulatory cytokines, adhesion molecules, and acute-phase proteins and an increase in pro-resolving mediators, indicating an anti-inflammatory effect elicited by the omega-3 fatty acids. GWAS of fish oil supplementation effects recently revealed new gene-diet interaction loci, some of which implicated in LDL metabolism (Francis et al 2021).…”
Section: Nutritional Effects On Transcriptionmentioning
confidence: 99%